Why is so difficult to coexist with passengers in the subway? - Beramendi, Maite Regina (2025)
This study explores the coexistence challenges among Buenos Aires subway passengers. It focuses on analyzing coexistence problems, perceptions, and participation in conflicts, as well as tolerance towards norm deviations. An online survey with 768 riders revealed that conflicts among passengers reproduce violence and create a social climate of mistreatment, normalizing disrespectful behaviors. Participants reported a stressful environment leading to contradictory behaviors: they are both vigilant and detached, paying less attention to others’ needs and more tolerance towards uncivil behavior. The findings suggest that the lack of adherence to social norms exacerbates the tense atmosphere, highlighting the need for better regulation and enforcement to improve passenger coexistence.